Transgenic Elephant Foot Yam (Amorphophallus paeoniifolius (Dennst.) Nicolson) Expressing Î²-glucuronidase Reporter Gene - Kamala, S; Thangaraj, Makeshkumar (JOURNAL OF ROOT CROPS, 2015)
Elephant foot yam (Amorphophallus paeoniifolius (Dennst.) Nicolson) is infected by various diseases such as mosaic, collar rot and dry rot disease, which cause severe yield reduction. Disease resistance can be achieved in crop plants through transgenic strategies. The present study is focused on Agrobacterium mediated transformation of A. paeoniifolius using Î²-glucuronidase (GUS) reporter gene. Friable callus cultures were established from corm lateral buds of A. paeoniifolius on modified Murashige and Skoog (MS) medium supplemented with 0.5 mg l-1 each of 6-Benzyl aminopurine, 2,4-Dichloro phenoxy acetic acid and Î±- Naphthalene acetic acid. Friable callus and swollen petiole explants were infected with Agrobacterium tumefaciens strain AGLO harbouring the Ti vector pOYE 153 having uidA gene encoding GUS. The transformation event was confirmed by GUS histochemical analysis and later on the presence of uidA gene was determined by Polymerase Chain Reaction (PCR). The highest transformation efficiency of 36.37% was observed for callus when compared to swollen petiole explant. The presence of acetosyringone improved the transformation efficiency by 20 fold irrespective of the explant. The present study serves as an initial step towards the development of transgenic A. paeoniifolius for disease resistance.